Implementasi Binarisasi Citra Menggunkan Metode K-Nearest Neighbor Untuk Mengindentifikasi Bawang Bombay Merah dan Bawang Bombay Putih - Rahmad, R; Syafril, S; Ramadhanu, Agung (LPPM STIKOM Tunas Bangsa, 2024)
The processing of digital image data is increasingly being developed and applied in various fields, one of which is object identification based on shape and color. This research aims to implement an image binarization method using the K-Nearest Neighbor (K-NN) method to identify two types of onions, namely red onions and white onions. The binarization method is used to convert color images into binary images, facilitating the feature extraction process. In this study, the features extracted from onion images include texture, shape, and color. K-NN is used as a classification algorithm to differentiate between the two types of onions based on these features. The results of the research indicate that the image binarization method and K-NN can identify red onions and white onions with a fairly high level of accuracy. The results of this implementation are expected to contribute to the development of an automatic recognition system for the classification of agricultural commodities.